2011
DOI: 10.1111/j.1477-9730.2011.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of uav systems and flight modes for photogrammetric applications

Abstract: Unmanned aerial vehicle (UAV) photogrammetry has been used in a growing number of diverse applications across different scientific disciplines. Early applications of UAVs included cultural heritage and archaeology, mainly for the documentation and modelling of monuments, buildings and landscapes. In this paper, the focus is on the application of UAVs for documenting archaeological excavations. As excavating is a dynamic process and the objects to be acquired can change significantly within a few hours, UAVs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(97 citation statements)
references
References 11 publications
0
92
0
2
Order By: Relevance
“…However, recent developments in military, remote control, hobby and opensource hardware have made it viable and potentially transformative to consider new small (1-5 kg), relatively inexpensive unmanned aerial vehicle (UAV) platforms for mapping glacier dynamics. UAV platforms include, helicopters, multirotors, fixed wings and paragliders; they are typically small (1-5 kg) and relatively cheap, ranging in cost from USD 400 to 20 000 (Eisenbeiß, 2009;Eisenbeiss and Sauerbier, 2011;Friedli, 2013). These platforms may be operated by remote control, first person or GPS-enabled autopilot systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent developments in military, remote control, hobby and opensource hardware have made it viable and potentially transformative to consider new small (1-5 kg), relatively inexpensive unmanned aerial vehicle (UAV) platforms for mapping glacier dynamics. UAV platforms include, helicopters, multirotors, fixed wings and paragliders; they are typically small (1-5 kg) and relatively cheap, ranging in cost from USD 400 to 20 000 (Eisenbeiß, 2009;Eisenbeiss and Sauerbier, 2011;Friedli, 2013). These platforms may be operated by remote control, first person or GPS-enabled autopilot systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Lumix GF3 RGB camera, another sensor will be used on the platform, enabling the generation of stereo images. See Aber et al (2010), Eisenbeiss et al (2005) and Eisenbeiss and Sauerbier (2011) for examples on DEM generation from stereo images collected by UAV. Furthermore, a combination of the data collected with different ground measurements such as hyper-spectral data or chlorophyll data is possible to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D reconstruction pipeline processes an automated tie point extraction, a bundle adjustment for camera parameters derivation, a dense image matching for surface reconstruction and a subsequent ortho-images generation. Many other studies have been carried on (Bäumker & Przybilla, 2011;Eisenbeiss & Sauerbier, 2011;Küng et al, 2011;Haala & Rothermel, 2012;Fiorillo et al, 2013;Nocerino et al, 2013) and have demonstrated the potential of the UAVs in the survey field, ensuring precision and accuracy in operations in which data acquisition is made difficult because of both the extension of the study area and reasons of inaccessibility. These systems allow the record of detailed information faster than other acquisition systems such as the range-based ones.…”
Section: Related Work and Work Aimsmentioning
confidence: 99%